Developing Students’ Worksheet Based Educational Comic for Eleventh Grade of Vocational High School Agriculture - Suhono, Suhono; Sari, Defika Andriana (Anglophile Journal, 2020)
This article was development students’ worksheet based educational comic for eleventh grade of vocatational high school (SMK) agriculture in Bumi Nabung.The development research model used is 4D which stands for Define, Design, Development and Disseminate. Based on the data analysis of the research obtained an average final score by media experts of 69 that is very worth category, on average by material experts of 44 that is worth category, average by language expert of 36 that is worth category, as well as testing students' worksheets conducted on 5 students obtained an average value of 71,6 that is very worth category. This shows that the developed teaching materials are suitable to be used as teaching materials in teaching and learning activities. Keywords : Developing, Students' Worksheets, Educational Comic